PENGARUH KETERLIBATAN KERJA TERHADAP KINERJA DENGAN PEMEDIASI KOMITMEN ORGANISASIONAL - Septiadi, Sebastianus Alexander; Sintaasih, Desak Ketut; Wibawa, I Made Artha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017DO - 10.24843/EEB.2017.v06.i08.p07, 2017)
This study examined the effect of job involvement on job performance and organizational commitment as mediation. This study involved 135 respondents and using saturated sample which take all employee become a respondents. Likert Scale is used as a balanced assessment questionnaires and using validity and reliability for testing questionaires. The analysis tool in the research is Structural Equation Model (SEM) which using a variance-based approach with Partial Least Square (PLS) as well as to test the mediating variable VAF to testing. Result of study found that job involvement has a positive effect on organizational commitment and job performance at Defense of Ministry. Organizational commitment has positive influence on job performance at Pusat Keuangan and organizational commitment as Partial mediation proved directly affect the relationship between job involvement and job performance. can be given to the Defense of Ministry is increasing attention to the dimensions of salary, normative commitment, and discipline work as dimensions that have bad perception
Keywords: Job Involvement, Organizationl Commitment and Job Performance